LESSONS LEARNED FROM THE MID-TERM EVALUATION OF THE AUSTRIAN NATIONAL STRATEGY FOR THE FRUIT AND VEGETABLES SECTOR - Hambrusch, Josef; Weber, Nina (Economics of Agriculture, 2014)
The Austrian national strategy for the fruit and vegetable sector provides a framework for the producer organisations sustainable operational programmes. One main objective of the national strategy is the bundling of production in order to improve the competitiveness of the fruits and vegetables producers. According to the agricultural census 2010, the share of production value of producer organisations in the fruit and vegetables sector, has constantly risen since 1999 and amounted to 53% in 2010. When analysing the number of projects and the expenditure of funds, it was found that a majority of financial resources was invested into the improvement of marketing activities / conditions and product quality. In order to justify ongoing public support in future, it will become necessary to stress the benefits of the operational programmes for the general public. This could be achieved, for example, by focusing on environmental measures. Already, integrated production has become the standard production method in the sector. Other environmental measures within the national strategy aimed at the reduction of resources in production (such as pesticides or energy). For these measures no improvements could be measured due to lacking monitoring data. For future evaluations, indicators need to be defined more clearly and precisely, in order to make the achievement of objectives measurable and visible.